Plant Growth and Morphological Characters of Sonchus arvensis L. from Different Chicken Manure Rates and Harvest Intervals with Ratooning Practices - Melati, Maya; Ari, Ahmad Nur Hidayat Gena; Aziz, Sandra Arifin (Journal of Tropical Crop Science, 2021)
Sonchus arvensis L., commonly known as perennial sow thistle, field milk thistle, among other names, is a weedy species that has medicinal values. Belongs to the Daisy family (Asteraceae), S. arvensis has a rosette form and it can be harvested more than once. The determination of harvest interval for ratoon of S. arvensis is necessary because ratooning can save time to produce the consecutive plant biomass, but the second harvest must be conducted at the correct time as it will determine the quantity and quality of leaves. As source of herbal medicine, cultivation of S. arvensis with organic fertilizer is preferred, and determination of organic fertilizer rates is also important for ratooning. The purpose of the study was to evaluate the plant growth response and yield with different chicken manure rates and different harvest intervals. The field experiment was conducted at IPB experimental station in Cikarawang, Darmaga Bogor, Indonesia. The study used a randomized complete block design with different manure rates (0, 7, 14, 21 ton.ha-1) and various harvest intervals (6, 8, and 10 weeks after the first harvest) as treatments. The results showed that for the first harvest, the effect of chicken manure rates was linear almost on all variables. For the ratoon (second harvest), manure rate of 14 ton.ha-1 (for first harvest) added with 4 ton.ha-1 (after first harvest) was enough for leaf production. The results indicate that ratoon should be harvested at 10 weeks after the first harvest to obtain the highest yield. The interaction between manure rates and harvest interval was not significant for growth variables of the second harvest.